1995
DOI: 10.1111/j.1748-5827.1995.tb02850.x
|View full text |Cite
|
Sign up to set email alerts
|

Canine eosinophilic folliculitis and furunculosis in three cases

Abstract: The historical, clinical and histopathological features of three dogs with eosinophilic folliculitis and furunculosis are described. The disease was characterised by the rapid development of pruritic, papular, pustular and ulcerative lesions on the dorsum of the muzzle. Skin lesions were confined to the face in two cases. The third dog had more generalised pustular lesions. Skin biopsy specimens showed marked eosinophil infiltration particularly centred on pilosebaceous units. Dermal collagen necrosis was evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…1,3,5,8,11 Depending on the severity of the lesion, epidermal hyperplasia, erosions, ulcerations, and variable amounts of spongiosis and necrosis may be present. 6,9,12,13 The so-called "flame figures," collagen fibers surrounded by degranulated eosinophils, are a commonly described finding but are not unique to this condition. 2,3,5,9 The histopathological appearance can vary but is consistent within the location of the lesion and its chronicity and severity.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,5,8,11 Depending on the severity of the lesion, epidermal hyperplasia, erosions, ulcerations, and variable amounts of spongiosis and necrosis may be present. 6,9,12,13 The so-called "flame figures," collagen fibers surrounded by degranulated eosinophils, are a commonly described finding but are not unique to this condition. 2,3,5,9 The histopathological appearance can vary but is consistent within the location of the lesion and its chronicity and severity.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical signs include peracute development of papules, pustules and crusts affecting face, pinnae and in particular the muzzle/bridge of the nose, hence the term “face rot.” Rarely, the abdomen or chest may also be affected and the condition can be painful or pruritic with localized swelling, ulceration, haemorrhage and fever. Permanent scarring is possible …”
Section: Insect Bite Hypersensitivitymentioning
confidence: 99%
“…Diagnosis is achieved through history, clinical examination, cytology and histology. Differential diagnoses include bacterial pyoderma or demodicosis . Many patients also have eosinophilia, and in one study, 50% of cases also had gastrointestinal symptoms …”
Section: Insect Bite Hypersensitivitymentioning
confidence: 99%
“…For example, Olivry et al (11) reported that the skin infiltrate of canine atopic dermatitis consists of mast cells, dendritic cells, memory helper T lymphocytes, neutrophils, and eosinophils. Furthermore, Curtis et al (12) reported that the eosinophil is the predominant cell type in several cases of folliculitis and furunculosis. Recently, it was reported that IL-5 mRNA could be detected in skin biopsy homogenates from dogs with atopic dermatitis.…”
Section: Introductionmentioning
confidence: 97%